Chemical composition and in vitro digestibility of some selected under-utilized tropical seeds as protein sources in ruminants’ diet - Omotoso, Oluwatosin Bode (2023)
From the results, raw Tomentosa nilotica and Monodora myristica have the highest crude protein (30.35% CP) and fat (22.40% EE), respectively. It is noteworthy that roasting best improve the mineral and significantly reduce the anti-nutrients observed in this study better compared to boiling and soaking methods. The highest organic matter digestibility, short-chain fatty acids, metabolizable energy and in vitro dry matter digestibility values were obtained in Dioclea reflexa compared to other test seeds. Roasting best improved the nutritive values, while Dioclea reflexa seed was rated highest for all the nutritional attributes and in vitro digestibility.